2001
DOI: 10.1074/jbc.m106605200
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,3,4-Trisphosphate 5/6-Kinase Is a Protein Kinase That Phosphorylates the Transcription Factors c-Jun and ATF-2

Abstract: Phosphorylation of inositol 1,3,4-trisphosphate by inositol 1,3,4-trisphosphate 5/6-kinase is the first committed step in the formation of higher phosphorylated forms of inositol. We have shown that the eight proteins called the COP9 signalosome complex copurify with calf brain 5/6-kinase. Because the complex has been shown to phosphorylate c-Jun in vitro, we tested both the complex and 5/6-kinase and found that both are able to phosphorylate c-Jun and ATF-2 on serine/threonine residues. These findings establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 48 publications
3
78
0
1
Order By: Relevance
“…The COP9 signalosome has been implicated in regulation of the cell cycle, proteolysis in the proteasome, and plant development (11)(12)(13). We have shown that 5/6-kinase associates with the CSN1 subunit of the COP9 signalosome and phosphorylates I B␣ and c-Jun (9,10). I B␣ phosphorylation is an important regulatory mechanism for TNF␣ 1 -induced NF-B activation.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The COP9 signalosome has been implicated in regulation of the cell cycle, proteolysis in the proteasome, and plant development (11)(12)(13). We have shown that 5/6-kinase associates with the CSN1 subunit of the COP9 signalosome and phosphorylates I B␣ and c-Jun (9,10). I B␣ phosphorylation is an important regulatory mechanism for TNF␣ 1 -induced NF-B activation.…”
mentioning
confidence: 94%
“…In addition, 5/6-kinase has been reported to phosphorylate inositol 3,4,5,6-tetrakisphosphate to inositol 1,3,4,5,6-pentakisphosphate (8). Recently, we have reported that 5/6-kinase also exhibits protein kinase activity and associates with the COP9 signalosome complex (9,10). The COP9 signalosome has been implicated in regulation of the cell cycle, proteolysis in the proteasome, and plant development (11)(12)(13).…”
mentioning
confidence: 99%
“…The CSN complex associates with multiple protein kinases capable of phosphorylating c-Jun (Uhle et al, 2003;Wilson et al, 2001). CSN2 and CSN5 promote (Claret et al, 1996;Naumann et al, 1999;Pollmann et al, 2001), while CSN1 inhibits AP-1 activation (Tsuge et al, 2001; this study).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that CSN1 can repress UV and serum induced expression of c-fos-lacZ chimeric gene in mouse fibroblast cells (Tsuge et al, 2001). In addition, CSN1 was shown to mediate interaction of CSN complex with 5/6-kinase, which can phosphorylate c-Jun and ATF-2 (Wilson et al 2001;Sun et al 2002). Moreover, ectopic expression of CSN1 was shown to inhibit the CSN-associated 5/6-kinase activity (Sun et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation